The 21st Century Skills of Elementary School Students in 3T Regions (Frontier, Outermost, and Least Developed Regions) - Daga, Agustinus Tanggu; Wahyudin, Dinn; Susilana, Rudi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research aims to analyze the 21st-century skills of students based on region and school accreditation status in the 3T regions. The method used is a survey with a quantitative-comparative approach. The sample of this study was 1281 elementary school students in the Southwest Sumba Regency. The research instrument was a questionnaire using data analysis techniques including descriptive statistics, normality and homogeneity tests, and hypothesis testing. The results of this study found that (1) there were differences in students’ 21st-century skills based on region and school accreditation; (2) by region, hypothesis testing showed that there was no significant difference in critical thinking skills but there was a significant difference in collaboration, communication, and creativity skills; (3) by accreditation, hypothesis testing shows a significant difference in critical thinking skills, collaboration, communication, creativity. Overall, this study provides evidence that the 21st-century skills of students in cities were higher than students in sub-districts and villages, as well as students in schools C-accredited higher than students in schools B-accredited B and unaccredited. This research has implications for the quality and performance of teachers both in designing the curriculum and facilitating the learning process to improve students’ abilities and skills.